2017
DOI: 10.1248/bpb.b17-00145
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccine Therapy Using Tumor Endothelial Cells as Antigens Suppresses Solid Tumor Growth and Metastasis

Abstract: Tumor angiogenesis plays an important role in tumor growth and metastasis, with tumor cells requiring nutrients and oxygen via blood flow for their proliferation. In comparison, angiogenesis also occurs under normal physiological conditions, such as wound healing and in the formation of the corpus luteum. Herein, we report on the development of a novel dendritic cell (DC) vaccine therapy using tumor endothelial cells (TECs) derived from tumor vessels as tumor antigens. After density gradient centrifugation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Our previous studies elucidated that DC immunization, using the TEC-rich-containing fraction separated from tumor tissues as antigenic proteins, showed anti-tumor effects by inhibiting angiogenesis in tumor tissues. 18,19) In addition, we demonstrated that DC immunization with the TEC-richcontaining fraction did not affect physiological angiogenesis during wound healing. 18) These results indicate that a specific tumor-associated antigen exists in the in vitro TEC model.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our previous studies elucidated that DC immunization, using the TEC-rich-containing fraction separated from tumor tissues as antigenic proteins, showed anti-tumor effects by inhibiting angiogenesis in tumor tissues. 18,19) In addition, we demonstrated that DC immunization with the TEC-richcontaining fraction did not affect physiological angiogenesis during wound healing. 18) These results indicate that a specific tumor-associated antigen exists in the in vitro TEC model.…”
Section: Discussionmentioning
confidence: 76%
“…18,19) In addition, we demonstrated that DC immunization with the TEC-richcontaining fraction did not affect physiological angiogenesis during wound healing. 18) These results indicate that a specific tumor-associated antigen exists in the in vitro TEC model. In the future, identification of specific antigen expressed in TECs derived from human is promising for the development of tumor blood vessel selective therapeutics such as TEC-specific antibodies and vaccine therapy for clinical trial.…”
Section: Discussionmentioning
confidence: 76%
“…1) In the process of tumor angiogenesis, tumor cells, fibroblasts and epithelial cells secrete vascular endothelial growth factor (VEGF), basic fibroblast growth factor, hepatocyte growth factor, or epidermal growth factor (EGF), and endothelial cells (ECs) are recruited from neighboring, pre-existing vasculatures in the tumor microenvironment. [2][3][4][5] In our previous study, we showed that cancer immunotherapy with TECs isolated from solid tumors suppressed tumor growth via the prevention of new blood vessel formation. 6) Tumor blood vessels also have a role as conduits for cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In that case, inhibiting angiogenesis is essential for the spread and deterioration of tumors. 22 Using these assays, we examined the potential of 5-acetamido-1-(methoxybenzyl) isatin to be used as an effective anti-tumor agent in multiple aspects.…”
Section: Introductionmentioning
confidence: 99%